Localization of Diacylglycerol Lipase-α around Postsynaptic Spine Suggests Close Proximity between Production Site of an Endocannabinoid, 2-Arachidonoyl-glycerol, and Presynaptic Cannabinoid CB1 Receptor - Yoshida, Takayuki (J Neurosci, 2006)
2-Arachidonoyl-glycerol (2-AG) is an endocannabinoid that is released from postsynaptic neurons, acts retrogradely on presynaptic cannabinoid receptor CB1, and induces short- and long-term suppression of transmitter release. To understand the mechanisms of the 2-AG-mediated retrograde modulation, we investigated subcellular localization of a major 2-AG biosynthetic enzyme, diacylglycerol lipase-α (DAGLα), by using immunofluorescence and immunoelectron microscopy in the mouse brain. In the cerebellum, DAGLα was predominantly expressed in Purkinje cells. DAGLα was detected on the dendritic surface and occasionally on the somatic surface, with a distal-to-proximal gradient from spiny branchlets toward somata. DAGLα was highly concentrated at the base of spine neck and also accumulated with much lower density on somatodendritic membrane around the spine neck. However, DAGLα was excluded from the main body of spine neck and head. In hippocampal pyramidal cells, DAGLα was also accumulated in spines. In contrast to the distribution in Purkinje cells, DAGLα was distributed in the spine head, neck, or both, whereas somatodendritic membrane was labeled very weakly. These results indicate that DAGLα is essentially targeted to postsynaptic spines in cerebellar and hippocampal neurons, but its fine distribution within and around spines is differently regulated between the two neurons. The preferential spine targeting should enable efficient 2-AG production on excitatory synaptic activity and its swift retrograde modulation onto nearby presynaptic terminals expressing CB1. Furthermore, different fine localization within and around spines suggests that the distance between postsynaptic 2-AG production site and presynaptic CB1 is differentially controlled depending on neuron types.